Disease flare patterns and predictors of systemic lupus erythematosus in a monocentric cohort of 423 Japanese patients during a long-term follow-up: The JUDE study. Issue 1 (2nd January 2017) - Minowa, Kentaro; Amano, Hirofumi; Ando, Seiichiro; Watanabe, Takashi; Ogasawara, Michihiro; Kawano, Shinya; Kaneko, Toshiyuki; Morimoto, Shinji; Yamaji, Ken; Tamura, Naoto; Tokano, Yoshiaki; Hashimoto, Hiroshi; et al.
Abstract: Objective : To clarify the clinical features of systemic lupus erythematosus (SLE) patients, factors associated with flares, and changes over time. Methods : Patients having SLE with a visiting history were entered into the Juntendo University Database of Erythematosus. We included 423 cases in the long-term follow-up analysis, and 383 cases were followed for 10 years after the initiation of any therapeutic intervention (comparative analysis: 1973–1982, 82 cases; 1983–1992, 141, and 1993–2002, 160). We assessed changes in the patients' background characteristics, disease symptoms, flare rates, etc. Results : Among the 423 cases, the mean follow-up period was 25.9 years, and mean number of flares was 0.51. Of those, 31.9% had ≥1 flares. Thrombocytopenia at onset contributed to the flares. For disease symptoms at onset, a recent trend in increasing thrombocytopenia was observed. The combination rate of immunosuppressive agents for diseases other than lupus nephritis was slightly increased, and there was no improvement until the first flare or in the flare rate. Conclusions : Thrombocytopenia at onset is predictive factor for flares. Since SLE is a diverse disease with varying symptoms at recurrence, the treatment guidelines should be improved for thrombocytopenia from a long-term perspective.